The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1590/s1678-9946201860024
|View full text |Cite
|
Sign up to set email alerts
|

Focal persistence of soil-transmitted helminthiases in impoverished areas in the State of Piaui, Northeastern Brazil

Abstract: This study aims to describe the prevalence, distribution, and factors associated with soil-transmitted helminthiases (STHs) in rural localities in Piaui, Brazil. Two cross-sectional surveys (n=605 subjects; 172 families) were carried out in order to obtain socio-demographic, anthropometric, spatial and parasitological data. Parasites were evaluated using Kato-Katz and centrifugal sedimentation techniques. Eggs were measured to assess infection with zoonotic Strongylida parasites. Kernel maps were constructed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 26 publications
(25 reference statements)
4
8
0
Order By: Relevance
“…In NSN-PI, pigs live in close proximity to human dwellings, having free access to houses and streets, so it is to be expected that humans and pigs were infected with the same Ascaris haplotype. Intriguingly, in NSN-PI, no human infection was observed with this parasite in the more than 600 analyzed samples [42]. Thus, we could not characterize the zoonotic circulation in communities where the rate of positivity in pigs was high.…”
Section: Discussionmentioning
confidence: 96%
“…In NSN-PI, pigs live in close proximity to human dwellings, having free access to houses and streets, so it is to be expected that humans and pigs were infected with the same Ascaris haplotype. Intriguingly, in NSN-PI, no human infection was observed with this parasite in the more than 600 analyzed samples [42]. Thus, we could not characterize the zoonotic circulation in communities where the rate of positivity in pigs was high.…”
Section: Discussionmentioning
confidence: 96%
“…Crowded families in the impoverished rural areas could act as hotspots of intestinal helminthic infections, despite the preventive chemotherapy as observed by a recent study from Brazil [15]. This highlights the significance of overcrowding in the human–human transmission of infection and maintenance of the parasite.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, almost a third of children had used drugs such as albendazole and mebendazole during the six months before faecal examination. Despite this, studies have demonstrated that in certain regions of Brazil-mainly in rural areas-some STH foci persist [23,24]. e administration of anthelmintic drugs without appropriate diagnostic tests has made it difficult to diagnose infection with protozoa, making giardiasis and amoebiasis underdiagnosed diseases.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, almost a third of children had used drugs such as albendazole and mebendazole during the six months before faecal examination. Despite this, studies have demonstrated that in certain regions of Brazil—mainly in rural areas—some STH foci persist [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%